KEPEMIMPINAN KEPALASEKOLAHDAN KOMPENSASI SERTA PENGARUHNYA TERHADAP MOTIVASI DAN KINERJA GURU - Tika Nurmala Sari (Manajemen dan Bisnis, 2019)
The weakness of teachers performance is unresolved untill present. Various studies held to identificate factors that hadcontrtibution  to increase teacher performance. In this  study head master leadership and teacher motivation were the factors expected had an effect to teacher performance  This study applied descriptive methode with quantitive strategy. Sample collected byStratified Proporsional random Sampling technique. The data collecting technique used literatures studies, questionnaires and observation.The result of study show thatpartially, leadership did not affect positively and significant to teacher performance.Compensation did not affect positively and significant to teacher performance. Motivation affected positively but not significant to teacher performance. Simultaneous, leadership, compensationand motivation affected to teacher motivation.Keywords: Leadership, compensation, motivation and performance